Analisis Data Pengeluaran Mahasiswa di Uinsu untuk Meningkatkan Perencanaan Keuangan - Anggi Safitri Lubis; Fawwaz Akif Prayoga; Nurbaiti Nurbaiti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the spending patterns of students at the Faculty of Islamic Economics and Business (FEBI), State Islamic University of North Sumatra (UINSU), and to examine the implementation of personal financial planning in their daily lives. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with 40 students from various departments and semesters, selected purposively. The findings indicate that most students have high expenditures on consumption needs such as food and internet access, as well as lifestyle expenses like online shopping and entertainment. The majority do not regularly prepare a financial budget, rarely record their expenses, and exhibit impulsive spending behavior influenced by social pressure and digital media. Although students possess theoretical knowledge of Islamic economic values, their practical application in financial management remains limited. This study recommends the need for more practical, Islam-based financial literacy programs within the FEBI UINSU environment. Financial training and mentoring programs are considered essential to enhance students' financial awareness and independence.